ChemInform Abstract: Asymmetric Hydroalkoxylation of Non‐activated Alkenes: Titanium‐Catalyzed Cycloisomerization of Allylphenols at High Temperatures. Issue 30 (July 2015) - Schlueter, Johannes; Blazejak, Max; Boeck, Florian; Hintermann, Lukas
Abstract A microwave‐assisted enantioselective intramolecular hydroxyalkylation of 2‐allylphenols at high temperatures yields 2‐methylcoumarans.